The expanding UPIS constitutional and policy issues - Pacquing, Alfonso G.
This lecture consists of three parts: part I, the constitutional issues; part II, the policy issues; and part III, the policy alternatives open to the university on the UPIS. The constitutional issues arise from two policy decisions of the Board of Regents of the university: (1) the UPIS policy on admission granting preference to children of UP faculty members and employees from grade K to 10; and (2) the UPIS policy on charging of fees with respect to pupils enrolled from K to 6. The second part of this lecture is an analysis of the wisdom of propriety of continuing the UPIS policy on admission preferring children of UP personnel over the children of non-UP personnel. The third part of this lecture tackled on the policy alternatives open to the university. Using Lewin's field theory and Corpuz view that policy making is bargaining as the modes of analysis.
Keywords: University of the Philippines (Diliman). Integrated School; University of the Philippines (Diliman). Integrated School -- Admission